Rhizosphere effects and microbial N limitations drive the root N limitations in the rhizosphere during secondary succession in a Pinus tabuliformis forest in North China - Duan, Songlan; Guo, Jinping; Zhang, Yunxiang; Liu, Libao; Wang, Rui; Zheng, Rongrong (Frontiers in Plant Science, 2024)
Rhizosphere effects (REs) have recently been identified as important regulators of root and microbial nutrient acquisition, and are positively involved in nutrient cycling of belowground carbon (C), nitrogen (N), and phosphorus (P). Nutrient conditions of the fine roots and soil N, are likely to influence REs. Still, it is unclear how REs of soil nutrients themselves variably impact the supply of nutrients to plants in terms of the responses to soil N due to succession. In this study, we applied both fine roots and extracellular enzymes for vector analysis and stoichiometry of N:P to explore the metabolic limitations of roots and rhizospheric soil microbes and their relationships with REs across five levels of soil N (0, 5, 10, 15, 20 kg N m-2 year-1) along successional age classes of 42-, 55-, and 65-years in a Pinus tabulaeformis forest. Overall, the metabolism of root and rhizosphere soil microbes was mediated by soil N. N limitation of roots initially decreased before increasing, whereas that of microbes demonstrated opposite trends to the N levels, owing to competition for inorganic N between them by REs of NO3-−N. However, N limitations of both roots and microbes were alleviated in young stands and increased with succession after the application of N. In addition, root N limitations were manipulated by REs of three different soil N-related indicators, i.e., total N, NH4+−N, and NO3-−N. Rhizospheric soil microbial N limitation was almost unaffected by REs due to their strong homeostasis but was an important driver in the regulation of root N limitation. Our results indicated that successional age was the most critical driver that directly and indirectly affected root N metabolism. However, the level of N application had a slight effect on root N limitation. Microbial N limitation and variations in the REs of N indicators-regulated root N limitation in the rhizosphere. As a result, roots utilized REs to sequester N to alleviate N limitations. These findings contribute to novel mechanistic perspectives on the sustainability of N nutrition by regulating N cycling in a system of plant-soil-microbes in the rhizosphere to adapt to global N deposition with succession.